SUBTITUSI TEPUNG TERIGU DENGAN TEPUNG UBI BANGGAI (Dioscorea spp) TERHADAP MUTU ORGANOLEPTIK BISKUIT - Fitriani Basrin; Tomotius Babe (Jurnal Pengolahan Pangan, 2019)
This study aims to determine the effect of substitution of wheat flour with proud cassava flour (dioscorea spp) on organoleptic quality of biscuits. The treatment design in the substitution study of wheat flour with proud yam flour (dioscorea spp) on the quality of organoleptic biscuits is: P0 (400 grams wheat of flour), P1 (100 grams of Banggai yam flour + 300 grams of wheat flour), P2 (200 grams of Banggai yam flour + 200 grams of wheat flour), P3 (300 grams of Banggai yam flour + 100 grams of wheat flour), and P4 (400 grams of Banggai yam flour). The experimental design used was Randomized Block Design (CRD) with 5 treatments and 4 replications. The organoleptic test results that included the most preferred taste, color, texture, and aroma were P1 biscuits (100 grams of Banggai yam flour + 300 grams of wheat flour) with an average value of 5.02 (rather like), color 4.56 (normal / neutral) , texture 4.86 (normal / neutral), and aroma 4.57 (normal / neutral).